Assessing the Impact of Entrepreneurship Education Programs: Challenges and Approaches. (13th June 2013) - Duval‐Couetil, Nathalie; Vozikis, George; Solomon, George; Winkel, Doan
<x xml:space="preserve">Abstract</x> Entrepreneurship education programs are increasingly being established and expanded in an effort to equip students with the knowledge and competency necessary to create economic value and jobs. An underlying assumption of these programs is that they create positive outcomes for students; however, the extent and nature of these outcomes have not been well explored in the literature. The purpose of this paper is to provide an overview of contemporary trends in educational evaluation and the challenges specifically associated with the assessment of entrepreneurship education programs. It proposes practical considerations for faculty and administrators involved in developing assessment initiatives for entrepreneurship education programs, including, the importance of reaching consensus on learning outcomes, the use of a stakeholder‐driven approach for setting assessment priorities, and the need to allocate resources to assessment initiatives so they can be sustained long term. It also highlights the value of involving faculty in the program evaluation process and the need to create incentives and opportunities for more assessment‐related research and scholarship within the field.